2009
DOI: 10.1063/1.3126936
|View full text |Cite
|
Sign up to set email alerts
|

Determination and comparison of kinetic parameters of low density biomass fuels

Abstract: Biomass has great potential as a clean, renewable feedstock for producing modern energy carriers. Low density biomass, such as rice husk, sawdust, bamboo dust, etc., can provide a continuous supply of liquid and gaseous fuels through thermochemical conversion processes. In the present study, kinetics of the thermal decomposition of three biomasses such as rice husk, sawdust, and bamboo dust were evaluated under air atmosphere from ambient temperature to 1000 °C at a heating rate of 10 °C min−1. Two distinct re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…It is attributed to dehydroxylation of kaolin to form metakaolin and dehydroxylation of illite due to the disruption of structural hydroxyl groups in clay. The main components of wood sawdust are hemicellulose, cellulose, and lignin, and these components are decomposed at different temperature ranges [22]. The TGA results of the sawdust showed that the moisture loss (about 5%) took place up to 100 8C followed by pyrolysis.…”
Section: Characterization Of the Raw Materials And Slurry Mixturesmentioning
confidence: 99%
“…It is attributed to dehydroxylation of kaolin to form metakaolin and dehydroxylation of illite due to the disruption of structural hydroxyl groups in clay. The main components of wood sawdust are hemicellulose, cellulose, and lignin, and these components are decomposed at different temperature ranges [22]. The TGA results of the sawdust showed that the moisture loss (about 5%) took place up to 100 8C followed by pyrolysis.…”
Section: Characterization Of the Raw Materials And Slurry Mixturesmentioning
confidence: 99%
“…Unfortunately, the boundary between the stages of volatile yield and the burnout of the coke residue for anthracite cannot be determined at all, since there is neither a change in the mass time change curve, nor a change in the derivative curve past 2000c (600 0 C) can be traced, (see Figure 1). Proceeding from the above, a number of foreign authors tried to analyze the entire process of thermal destruction of coal in the range 200 ÷ 800 0 С, as is done in [12], or to correct the constants by choosing the various orders of the reaction, as model fitting methods in [5,6]. However, the authors [12] provide kinetic equations in two temperature ranges, which indirectly indicate the presence of two distinct processes, and in [4] the whole destruction zone is divided into the region of pyrolysis and the actual burning of coke.…”
Section: Figure 1 Derivatogravitogram Of Anthracite Coal Thermal Desmentioning
confidence: 99%
“…It should be noted that today the topics of the kinetic studies of solid fuels thermal degradation became an undisputed leader among the research in the field of thermophysics of combustion and multidisciplinary studies on the processing and preparation of solid fuels in the energy sector [1][2][3][4][5][6][7][8]. This is due to the involvement of a variety of biomass types which is used as an alternative fuel in the national energy sectors of countries, both for the purpose of substantially expanding the market of energy resources and with the need to utilize a large amount of solid household waste, waste from the agrarian and food industries [1][2][3][4][5][6][7].Wide implementation of co-combustion technologies into the national power sectors renders revitalization effect on the environments, since the said technology allows a significant decrease of harmful substances release primarily into the atmosphere [10]. Knowledge of kinetic parameters becomes especially critical when designing units for co-firing of coal and solid biomass, especially for the pulverized coal combustion, since shredding biomass to the fineness of pulverized coal dust appears cost prohibitive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fast pyrolysis is a relatively new technology for converting whole biomass into complex liquid fuels (Kalita et al 2009). The bio-oil, produced from fast pyrolysis in yields up to 75 wt%, is a free flowing, complex mixture of water, organic acids, aldehydes, ketones, sugars, phenolics, and lignin derived oligomers (pyrolytic lignin).…”
Section: Hydrothermal Routementioning
confidence: 99%